Pharmacological Augmentation of Psychosocial and Remediation Training Efforts in Schizophrenia - Harvey, Philip D.; Sand, Michael (Frontiers in Psychiatry, 2017)
Pharmacological approaches to cognitive enhancement have received considerable attention but have not had considerable success in improving their cognitive and functional targets. Other intervention strategies, such as cognitive remediation therapy (CRT), have been shown to enhance cognitive performance but have not been found to improve functional outcomes without additional psychosocial interventions. Recently, several studies have attempted to enhance the effects of CRT by adding pharmacological interventions to the CRT treatments. In addition, as CRT has been shown to synergistically improve the effects of psychosocial interventions, the combination of pharmacological therapies aimed at cognition and psychosocial interventions may itself provide a promising strategy for improving functional outcomes. This review and commentary examines the current state of interventions combining CRT and psychosocial treatments with pharmacological augmentation. Our focus is on the specific level of effect of the pharmacological intervention, which could be enhancing motivation, training efficiency, or the consolidation of therapeutic gains. Different pharmacological strategies (e.g., stimulants, plasticity-inducing agents, or attentional or alertness enhancers) may have the potential to lead to different types of gains when combined with CRT or psychosocial interventions. The relative potential of these different mechanisms for immediate and durable effects is considered.